Media Brands and Branding : Media Management and Transformation C ENTRE - mart ots(ed) ([Place of publication not identified] : Jonkop.ing International Business School, 2008)
Strong brands are necessary in media because technology has increased the number of contenu p.roviders and made it p.ossible for many more comp.etitors to seek the attention and loyalty of audiences and advertisers brands are crucial in creating continuity of quality and service across extente p.roduct lines and in help.ing devlop. strong bonds with consumers
Keywords: the book; media